PELATIHAN APLIKASI PEMBUKUAN KEUANGAN PADA USAHA BANTEN UPAKARA IBU MANGKU KARTA DI KOTA DENPASAR - I Putu Widyarsana; Putu Eny Suhardiyani; I Gede Nika Wirawan (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2024)
The religious ceremonial activities of the Hindu community in Bali cannot be separated from offerings or what is known as banten or jasajen. To support the ceremony, the community needs various ceremonial offerings according to the level of the religious ceremony being carried out. The change in the lifestyle of the Balinese people from agricultural to industrial has changed the life structure of the Balinese people. At every religious ceremony, the Balinese Hindu community has switched to buying offerings for reasons of busy daily work, social activities, infrastructure, the influence of globalization, knowledge, and so on. This is what triggered the emergence of the upakara offering business. This time's service partner is Mrs. Mangku Karta who has managed the upakara offering business for around 6 years. Mitra sells upakara offerings at his house on Jalan Gatot Subroto I Denpasar. Based on the results of the interview, the partner does not have financial bookkeeping as an effort to record his business finances. Based on the partner's situation, the service proposing team has plans to carry out training on financial bookkeeping applications, namely recording all income and expenses related to financial activities including purchases, sales, operational costs, salaries and other transactions using Paper.id financial application. Based on the results of interviews regarding mastery of the material, it was discovered that participants had reached 95% mastery of the material. The output produced in this service is financial control or control which is carried out compulsorily and regularly in accumulating all types of financial data and information on partner businesses.